2011
DOI: 10.1002/j.0022-0337.2011.75.12.tb05221.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Dental Students in India About Smoking Cessation Counseling

Abstract: Smoking kills 900,000 people every year in India. Many studies have shown that counseling from a health professional is an effective method of helping patients quit. The aim of this study was to evaluate the knowledge and attitudes of dental students in Karnataka, India, towards smoking cessation counseling. A questionnaire study was conducted among a convenience sample of 329 dental students comprised of III year and IV year students and interns in three dental colleges in Karnataka, India. Of the 329 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 14 publications
2
33
2
Order By: Relevance
“…Some researchers suggest that students' experience in delivering oral health education to patients during undergraduate training could help them expand the prevention concept into holistic patient management. They would also be more likely to become interested in the overall well-being of their patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest that students' experience in delivering oral health education to patients during undergraduate training could help them expand the prevention concept into holistic patient management. They would also be more likely to become interested in the overall well-being of their patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use is single most preventable cause of morbidity and mortality globally (Rajasundaram et al, 2011;Salman et al, 2014). At present, tobacco usage is a global concern as the World Bank predicts over 450 million tobacco deaths in next 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…At present, tobacco usage is a global concern as the World Bank predicts over 450 million tobacco deaths in next 50 years. Tobacco cessation counselling by a health professional has been proven effective and it has been reported that appropriate assistance and professional advice by health professionals has led to a cessation rate of 10% -20% (Rajasundaram et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies mainly focused on one or a few aspects related to counselling for Tobacco cessation among dental students (Rajasundaram et al, 2011;Halawany et al, 2013;Murugaboopathy et al, 2013). Identifying various factors involved in counselling for Tobacco cessation independently alone may not be sufficient.…”
Section: Introductionmentioning
confidence: 99%